Dinamika pengambilan keputusan kepala sekolah dalam manajemen pesantren Salafiyah Kota Pekanbaru - Akhyar, Yundri (Universitas Muhammadiyah Magelang, 2025)
Effective decision-making is a key element in educational management, especially in Salafiyah pesantren, which are characterized by traditional and collective leadership. The headmaster plays a crucial role in establishing policies that influence various operational aspects of the pesantren. This study aims to analyze the decision-making patterns of headmasters, the factors influencing their decisions, and the impact on pesantren management effectiveness. This research employs a descriptive quantitative method using a questionnaire as the primary instrument. The respondents consist of 19 headmasters from Salafiyah pesantren in Pekanbaru, selected using total sampling. The results indicate that decision-making in pesantren follows a hierarchical and collective approach, involving teacher participation, deliberation (musyawarah), and consideration of pesantren traditions. The primary factors influencing decisions include pesantren values and traditions, government policies, and input from caretakers and ustaz. The headmaster's decisions significantly impact the effectiveness of pesantren management, particularly in improving learning quality, financial transparency, and student discipline.